1993
DOI: 10.1136/bmj.307.6917.1455
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal screening for trisomy 18 with free beta human chorionic gonadotrophin as a marker.

Abstract: Objective-To determine the relation between maternal serum cx fetoprotein and free 1 human chorionic gonadotrophin concentrations in pregnancies complicated by trisomy 18 IntroductionBiochemical screening for trisomy 21 can now identify 65-75% of cases early in the second trimester, particularly when combinations of a fetoprotein and free 1 human chorionic gonadotrophin concentrations are used as markers. 1-6The prospect of first trimester screening with these analytes to achieve detection rates exceeding 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 23 publications
4
23
2
Order By: Relevance
“…18 The birth prevalence rate of Edwards' syndrome varies considerably, from 1:3000 to 1:11,000 live births. 2,3,7,[19][20][21][22][23][24] In the present study, the T18 average birth prevalence rate was 8.95 per 10,000 live births, which is significantly higher than the previous rate reported from Kuwait during 1984-1985 (1.1 per 10,000) and in 1986 (4.61 per 10,000). 25 Although clustering of births of children with Edwards' syndrome has been previously reported, no studies reported such a high rate.…”
Section: Discussioncontrasting
confidence: 55%
“…18 The birth prevalence rate of Edwards' syndrome varies considerably, from 1:3000 to 1:11,000 live births. 2,3,7,[19][20][21][22][23][24] In the present study, the T18 average birth prevalence rate was 8.95 per 10,000 live births, which is significantly higher than the previous rate reported from Kuwait during 1984-1985 (1.1 per 10,000) and in 1986 (4.61 per 10,000). 25 Although clustering of births of children with Edwards' syndrome has been previously reported, no studies reported such a high rate.…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast to the slightly reduced or normal levels found in cases of trisomy 18, a case of trisomy 18 associated with omphalocele had an elevated level (3.37) in our study. Although inhibin A levels are low in trisomy 18, the reduction is too slight, unlike those of other serum markers with markedly reduced levels [31], to be used as a useful marker in the detection of fetal trisomy 18.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is required to determine whether a specific screen for trisomy 18 should be added to routine Down's screening programmes but it does appear likely that a specific screen may be beneficial. 4 …”
Section: Discussionmentioning
confidence: 99%